PpGpp influences protein protection, growth and photosynthesis in Phaeodactylum tricornutum. Issue 4 (19th March 2021) - Avilan, Luisana; Lebrun, Regine; Puppo, Carine; Citerne, Sylvie; Cuiné, Stephane; Li‐Beisson, Yonghua; Menand, Benoît; Field, Ben; Gontero, Brigitte
Summary: Chloroplasts retain elements of a bacterial stress response pathway that is mediated by the signalling nucleotides guanosine penta‐ and tetraphosphate ((p)ppGpp). In the model flowering plant Arabidopsis, ppGpp acts as a potent regulator of plastid gene expression and influences photosynthesis, plant growth and development. However, little is known about ppGpp metabolism or its evolution in other photosynthetic eukaryotes. Here, we studied the function of ppGpp in the diatom Phaeodactylum tricornutum using transgenic lines containing an inducible system for ppGpp accumulation. We used these lines to investigate the effects of ppGpp on growth, photosynthesis, lipid metabolism and protein expression. We demonstrate that ppGpp accumulation reduces photosynthetic capacity and promotes a quiescent‐like state with reduced proliferation and ageing. Strikingly, using nontargeted proteomics, we discovered that ppGpp accumulation also leads to the coordinated upregulation of a protein protection response in multiple cellular compartments. Our findings highlight the importance of ppGpp as a fundamental regulator of chloroplast function across different domains of life, and lead to new questions about the molecular mechanisms and roles of (p)ppGpp signalling in photosynthetic eukaryotes.